Requisitos técnicos da qualidade do nível de eficiência energética aplicado em edificação pública em fase de projeto: o caso do Centro de Convivência para Idosos em Doutor Maurício Cardoso - RS - Brum, Thaís Faccim de (2010)
The labeling of buildings specified by technical regulations of energy efficiency quality level s presents the technical requirements and the methods for the classification of commercial buildings, services and publics regarding energy efficiency. The work consisted in the application of this regulation in the design phase of the public building the will house the convenience center for elderly in town of Doutor Maurício Cardoso RS. Starting from the experience of application of regulation, was evaluated the applicability of it, from the viewpoint of the evaluator and, from the analysis of the influence of variables that determine the building s classification, was analyzed the application of regulations from the point of view of architectural practice. The prescriptive method, which is contained in regulations, was used for general and partial classification of efficiency levels of building. The three main requirements were considered, established by legislation: Envelopment, lighting and air conditioning system. In order to draw conclusions about the real influences of the variables that determine the efficiency level of the building were created hypothetical scenarios. The work presents itself as a major issue, since the application of the methodology of the regulations, can be used as a design tool, encouraging the use of energy efficient solutions from design architectural, contributing to the performance of increasingly efficient buildings vigorously. It was possible to observe, with the obtained results, regarding the applicability of the regulations, and some difficulties regarding the presentation the data necessary for such, the classification of naturally ventilated environments is prejudiced due to the numerical equivalent of ventilation that can only be obtained through simulation. Regarding the variables that determine the efficiency, stands out the negative ways behave in some variations of the angles of shadowing. In artificially conditioned buildings, the efficiency of the envelopment along with the conditioning system interfere with the classification, whereas the remaining transitional environments are not conditioned, aspect that also contributes to the efficiency.